Early transcriptional responses of bovine chorioallantoic membrane explants to wild type, ΔvirB2 or ΔbtpB Brucella abortus infection. - Juliana P S Mol (Public Library of Science (PLoS), 2014)
The pathogenesis of the Brucella-induced inflammatory response in the bovine placenta is not completely understood. In this study we evaluated the role of the B. abortus Type IV secretion system and the anti-inflammatory factor BtpB in early interactions with bovine placental tissues. Transcription profiles of chorioallantoic membrane (CAM) explants inoculated with wild type (strain 2308), ΔvirB2 or ΔbtpB Brucella abortus were compared by microarray analysis at 4 hours post infection. Transcripts with significant variation (>2 fold change; P<0.05) were functionally classified, and transcripts related to defense and inflammation were assessed by quantitative real time RT-PCR. Infection with wild type B. abortus resulted in slightly more genes with decreased than increased transcription levels. Conversely, infection of trophoblastic cells with the ΔvirB2 or the ΔbtpB mutant strains, that lack a functional T4SS or that has impaired inhibition of TLR signaling, respectively, induced more upregulated than downregulated genes. Wild type Brucella abortus impaired transcription of host genes related to immune response when compared to ΔvirB and ΔbtpB mutants. Our findings suggest that proinflammatory genes are negatively modulated in bovine trophoblastic cells at early stages of infection. The virB operon and btpB are directly or indirectly related to modulation of these host genes. These results shed light on the early interactions between B. abortus and placental tissue that ultimately culminate in inflammatory pathology and abortion.